Reverse Triangle Inequality
Theorem
Let $M = \struct {X, d}$ be a metric space.
Then:
- $\forall x, y, z \in X: \size {\map d {x, z} - \map d {y, z} } \le \map d {x, y}$
Normed Division Ring
Let $\struct {R, \norm {\,\cdot\,} }$ be a normed division ring.
Then:
- $\forall x, y \in R: \norm {x - y} \ge \bigsize {\norm x - \norm y}$
Normed Vector Space
Let $\struct {X, \norm {\, \cdot \,} }$ be a normed vector space.
Then:
- $\forall x, y \in X: \norm {x - y} \ge \size {\norm x - \norm y}$
Real and Complex Numbers
Let $x$ and $y$ be elements of either the real numbers $\R$ or the complex numbers $\C$.
Then:
- $\cmod {x - y} \ge \size {\cmod x - \cmod y}$
Seminormed Vector Space
Let $\struct {K, +, \circ}$ be a division ring with norm $\norm {\,\cdot\,}_K$.
Let $X$ be a vector space over $K$.
Let $p$ be a seminorm on $X$.
Then:
- $\forall x, y \in X : \size {\map p x - \map p y} \le \map p {x - y}$
This article, or a section of it, needs explaining. In particular: $\size {\map p x - \map p y}$ You can help $\mathsf{Pr} \infty \mathsf{fWiki}$ by explaining it. To discuss this page in more detail, feel free to use the talk page. When this work has been completed, you may remove this instance of {{Explain}} from the code. |
Proof
Let $M = \struct {X, d}$ be a metric space.
By Metric Space Axiom $(\text M 2)$: Triangle Inequality, we have:
- $\forall x, y, z \in X: \map d {x, y} + \map d {y, z} \ge \map d {x, z}$
By subtracting $\map d {y, z}$ from both sides:
- $\map d {x, y} \ge \map d {x, z} - \map d {y, z}$
Now we consider 2 cases.
- Case $1$
- Suppose $\map d {x, z} - \map d {y, z} \ge 0$.
Then:
- $\map d {x, z} - \map d {y, z} = \size {\map d {x, z} - \map d {y, z} }$
and so:
- $\map d {x, y} \ge \size {\map d {x, z} - \map d {y, z} }$
- Case 2
- Suppose $\map d {x, z} - \map d {y, z} < 0$.
Applying Metric Space Axiom $(\text M 2)$: Triangle Inequality again, we have:
- $\forall x, y, z \in X: \map d {y, x} + \map d {x, z} \ge \map d {y, z}$
Hence:
- $\map d {x, y} \ge \map d {y, z} - \map d {x, z}$
Since we assumed $\map d {x, z} - \map d {y, z} < 0$, we have that:
- $\map d {y, z} - \map d {x, z} > 0$
and so:
- $\map d {y, z} - \map d {x, z} = \size {\map d {y, z} - \map d {x, z} }$
Thus we obtain:
- $\map d {x, y} \ge \size {\map d {x, z} - \map d {y, z} }$
Since these cases are exhaustive, we have shown that:
- $\forall x, y, z \in X: \map d {x, y} \ge \size {\map d {x, z} - \map d {y, z} }$
$\blacksquare$
Sources
- 1975: W.A. Sutherland: Introduction to Metric and Topological Spaces ... (previous) ... (next): $2$: Continuity generalized: metric spaces: Exercise $2.6: 2$